2020
DOI: 10.20463/pan.2020.0014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mild-intensity exercise training with capsiate intake on fat deposition and substrate utilization during exercise in diet-induced obese mice

Abstract: While the anti-obesity effects of exercise and capsiate are well-observed individually, the effect of exercise with capsiate intake has not been systematically explored yet. Therefore, the purpose of this study is to investigate whether the anti-obesity effects of exercise training can be further enhanced by capsiate intake. [Methods] 8-week-old male mice were divided into 3 groups (n = 8 per group): sedentary group (SED; nontrained), exercise-trained group (EXE) and exercisetrained group with 10 mg/kg of caps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…Subsequently, the adrenaline and noradrenaline levels in blood were enhanced by acute treatment with capsiate in humans [ 22 ] and rodents [ 21 ]; consequently, the released catecholamines promoted fat utilization and thermogenesis [ 31 , 32 ]. Indeed, CI before exercise decreased the respiratory exchange rate and increased fax oxidation during exercise [ 33 ]; moreover, according to the results of the current study, the β3AR protein expression of EXE+CAP was significantly upregulated in adipose tissue. This indicated that the ability of lipolysis was enhanced.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Subsequently, the adrenaline and noradrenaline levels in blood were enhanced by acute treatment with capsiate in humans [ 22 ] and rodents [ 21 ]; consequently, the released catecholamines promoted fat utilization and thermogenesis [ 31 , 32 ]. Indeed, CI before exercise decreased the respiratory exchange rate and increased fax oxidation during exercise [ 33 ]; moreover, according to the results of the current study, the β3AR protein expression of EXE+CAP was significantly upregulated in adipose tissue. This indicated that the ability of lipolysis was enhanced.…”
Section: Discussionsupporting
confidence: 70%
“…Note that the data of BW, FI, and abdominal fat, the result of Table 1 , were coused with the previously published paper [ 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…To ensure that the exercise intensity is equally maintained throughout the entire experiment (equalization of relative exercise intensity), we had gradually increased the treadmill speed and/or exercise duration over time (increasing absolute exercise intensity; Fig. 1 B), based on our previous studies 33 35 . The increase in absolute exercise intensity is required because chronic exercise enhances the exercise ability (occurrence of an exercise adaptation), and the enhanced exercise ability subsequently leads to decrease in the relative exercise intensity if the absolute exercise intensity is not increased.…”
Section: Resultsmentioning
confidence: 99%
“…Prior to conducting the experiment, all groups were fasted for 8 h. The EXLA group was administered 3 g/kg of sodium lactate with an oral sonde and the EX group an equal amount of a saline solution [ 23 , 41 ]. The mice were orally administered the appropriate supplement 30 min before a moderate intensity (about 60–70% VO 2max ) exercise was conducted for 30 min (treadmill exercise at a speed of 18 m/min and slope of 6°) [ 42 , 43 ]. Immediately after exercise, the mice were anesthetized with 10 µL/g of 1.25% avertin and the tissues were collected.…”
Section: Methodsmentioning
confidence: 99%